Chlorhexidine Resistance or Cross-Resistance, That Is the Question - Hadeel Mohammed Abbood; Karolin Hijazi; Ian M. Gould (MDPI AG, 2023)
Chlorohexidine (CHX) is a widely used biocide in clinical and household settings. Studies over the last few decades have reported CHX resistance in different bacterial species, but at concentrations well below those used in the clinical setting. Synthesis of these findings is hampered by the inconsistent compliance with standard laboratory procedures for biocide susceptibility testing. Meanwhile, studies of in vitro CHX-adapted bacteria have reported cross-resistance between CHX and other antimicrobials. This could be related to common resistance mechanisms of CHX and other antimicrobials and/or the selective pressure driven by the intensive use of CHX. Importantly, CHX resistance and cross-resistance to antimicrobials should be investigated in clinical as well as environmental isolates to further our understanding of the role of CHX in selection of multidrug resistance. Whilst clinical studies to support the hypothesis of CHX cross-resistance with antibiotics are currently lacking, we recommend raising the awareness of healthcare providers in a range of clinical disciplines regarding the potential adverse impact of the unfettered use of CHX on tackling antimicrobial resistance.